2011
DOI: 10.1097/yic.0b013e32834967e5
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of benzodiazepine diversion using a multi-indicator approach

Abstract: Fourteen benzodiazepine (BZD) or BZD-like medications were analyzed with three data sources aiming to assess prescription drug abuse for the year 2008. After a descriptive analysis, a principal component analysis was carried out to explore correlations between seven indicators obtained by different methods using these three different data sources and to compute a composite score of diversion for these drugs. For all the indicators, flunitrazepam appears first with much higher values than the other drugs, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Previous studies have highlighted the importance of clonazepam as a diverted drug, but in a French study from 2011, it was only second to flunitrazepam [16]. Another French study from 2010 found that clonazepam was the third most frequently illegally obtained medicinal drug, after buprenorphine and methadone.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have highlighted the importance of clonazepam as a diverted drug, but in a French study from 2011, it was only second to flunitrazepam [16]. Another French study from 2010 found that clonazepam was the third most frequently illegally obtained medicinal drug, after buprenorphine and methadone.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of off-label use of these drugs, a survey on falsified prescriptions should help to monitor their patterns of use and/or misuse [50]. As recently shown with pregabalin [51,52], specific and permanent tools are needed in the area of monitoring of addiction, enabling a multiple-source approach to identify and quantify abuse of or dependence on prescription drugs [53]. …”
Section: Discussionmentioning
confidence: 99%
“…In the global literature, a range of terms are used to encapsulate prescription drug misuse including abuse, dependence, diversion, misuse, problematic or non-medical use [1,[28][29][30]. As such, our search strategies included twenty-four unique misuse-related terms to capture relevant articles.…”
Section: Terminologymentioning
confidence: 99%